Highly Efficient Aqueous Synthesis of Propargylamines through C–H Activation Catalyzed by Magnetic Organosilica‐Supported Gold Nanoparticles as an Artificial Metalloenzyme. Issue 22 (4th June 2018) - Aghahosseini, Hamideh; Tabatabaei Rezaei, Seyed Jamal; Tadayyon, Mahsa; Ramazani, Ali; Amani, Vahid; Ahmadi, Roya; Abdolahnjadian, Davod
Abstract : Highly efficient magnetic organosilica‐supported gold nanoparticles were developed as an artificial metalloenzyme for the synthesis of propargylamines through C–H activation in water under an ambient atmosphere. Herein, we present a very simple and efficient method for the deposition of Au nanoparticles on porous magnetic organosilica (Fe3 O4 @SiO2 ‐Cl) through the thermal reduction of an organometallic Au III complex. As a nucleophile, a Au III polypyridyl coordination complex could react with alkyl halides from the Fe3 O4 @SiO2 ‐Cl to form a quaternary ammonium salt as an ionic liquid; subsequently, the ligand was oxidized and the Au nanoparticles were embedded into the porous organosilica shell. The synergic effect of the gold nanoparticles as catalytically active sites, pyridinium chloride as a phase‐transfer agent, and the magnetite nanoparticle core, which could function as a protein mimic, endow the material with high efficiency, stability, recoverability, reusability, and good turnover frequency, all of which are necessary characteristic for an artificial enzyme. A reliable catalytic procedure for the synthesis of propargylamines was identified. Abstract : Highly efficient magnetic organosilica‐supported gold nanoparticles are prepared as an artificial metalloenzyme. The Au nanoparticles are deposited on porous magnetic organosilica through the thermal reduction of an organometallic Au III complex. This artificial metalloenzyme is employed for the synthesis of propargylamines through C–H activation in water under an ambient atmosphere.